Research progress of vitrified bond CBN grinding wheel - Hengheng WU; Qiao XU; Honggen ZHOU; Xiaoyan GUAN; Xiaona SHI; Guochao LI (Jin'gangshi yu moliao moju gongcheng, 2023)
The ceramic CBN grinding wheels are widely used in the fields of forming and precision machining, and the research on them is of great significance in improving the machining quality and efficiency of workpieces. The research progress of ceramic CBN grinding wheels in recent years is summarized from various aspects, including CBN abrasive grains, modifier addition, preparation and grinding performances. Additionally, the future development prospects are also discussed. Regarding CBN abrasive grains, the synthesis of CBN single crystal is explored, and the surface treatment of CBN abrasive grains, as well as the treatment methods when adding a strong magnetic field, are introduced. Concerning modifier, the influences of adding pore forming agents, oxides, metal materials and nano-materials on the performances of ceramic CBN grinding wheels are discussed. In the preparation of ceramic CBN grinding wheels, the methods of forming and sintering are described. Moreover, the grinding applications of ceramic CBN grinding wheels on difficult-to-machine materials such as steel, nickel base alloy and titanium alloy are introduced, and the factors affecting the grinding performances of CBN grinding wheels are proposed.